Category-dependent preferences and stochastic choice - Matthew Joseph Ryan (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2024)
We introduce a generalisation of Aguiarís (2017) random categorisation rule (RCR) that allows preferences to be category dependent. Our generalised random categorisation rule (GRCR) requires the preferences associated with two dierent categories to agree on their intersection. We show that this is equivalent to relaxing the completeness and transitivity requirement on the preference relation in the RCR model. The GRCR model is therefore characterised by relaxing Aguiarís (2017) Acyclicity axiom to an Asymmetry axiom. We also provide a characterisation of the model in terms of Block-Marschak polynomials. Finally, we show that a random choice function has a Manzini and Mariotti (2014) model i it has both a GRCR representation and a Brady and Rehbeck (2016) model.
Keywords: 330